5-year outcomes of patients with mitral structural valve deterioration treated with transcatheter valve in valve implantation. (3rd October 2022) - Schamroth Pravda, N; Mishaev, R; Levi, A; Witberg, G; Shapira, Y; Orvin, K; Talmor Barkan, Y; Hamdan, A; Sharoni, R; Perl, L; Sagie, A; Vaknin Assa, H; et al.
Abstract: : The Valve-in-Valve (ViV) technique is an emerging alternative for the treatment of bioprosthetic structural valve deterioration (SVD) in the mitral position. We report on intermediate-term outcomes of patients with symptomatic SVD in the mitral position who were treated by transcatheter mitral valve-in-valve (TM-ViV) implantation during the years 2010–2019 in our center. Three main outcomes were examined during the follow-up period: NYHA functional class, TM-ViV hemodynamic data per echocardiography, and mortality. Our cohort consisted of 49 patients (mean age 77.4±10.5 years, 65.3% female). The indications for TM-ViV were mainly for regurgitant pathology (77.6%). All 49 patients were treated with a balloon-expandable device. The procedure was performed via transapical access in 17 cases (34.7%) and transfemoral vein / trans-atrial septal puncture in 32 cases (65.3%). Mean follow-up was 4.4±2.0 years. 98% and 91% of patients were in NYHA I/II at 1 and 5 years respectively. Mitral regurgitation was ≥ moderate in 86.3% of patients prior to the procedure and this decreased to 0% (p<0.001) following the procedure and was maintained over 2 years follow-up. The mean trans-mitral valve gradients decreased from pre-procedural values of 10.1±5.1mmHg to 7.0±2.4mmHg at one month following the procedure (p=0.03). Mortality at one year was 16% (95%, CI 5–26) and 35% (95%, CI 18–49) at 5 years. ViV in the mitral position offers an effective and durable treatment option for patients with SVD at high surgical risk. Funding Acknowledgement: Type of funding sources: None.